2018
DOI: 10.1002/jcc.25338
|View full text |Cite
|
Sign up to set email alerts
|

Free energy landscapes of prototropic tautomerism in pyridoxal 5′‐phosphate schiff bases at the active site of an enzyme in aqueous medium

Abstract: We have performed hybrid quantum-classical metadynamics simulations and quantum chemical calculations to investigate the free energy landscapes of intramolecular proton transfer and associated tautomeric equilibrium in pyridoxal 5 '-phosphate (PLP) Schiff Bases, namely the internal and external aldimines, at the active site of serine hydroxymethyltransferase (SHMT) enzyme in aqueous medium. It is important to determine the relative stability of the two tautomers (ketoenamine and enolimine) of the PLP aldimines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 53 publications
(58 reference statements)
4
21
0
Order By: Relevance
“…The hydroxyl group of the serine substrate is found to be hydrogen bonded to the active site Glu′53 residue and the phenolic oxygen (O3A) is found to lie close to the active site Ser172 residue. Also, the external aldimine that is produced at the end of the transimination reaction is found to be in the ketoenamine form with proton staying with the imine nitrogen, which is consistent with the earlier results of the keto-enol tautomerism of the SER-PLP external aldimine at the active site of SHMT …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The hydroxyl group of the serine substrate is found to be hydrogen bonded to the active site Glu′53 residue and the phenolic oxygen (O3A) is found to lie close to the active site Ser172 residue. Also, the external aldimine that is produced at the end of the transimination reaction is found to be in the ketoenamine form with proton staying with the imine nitrogen, which is consistent with the earlier results of the keto-enol tautomerism of the SER-PLP external aldimine at the active site of SHMT …”
Section: Discussionsupporting
confidence: 91%
“…The phosphate group of PLP is deeply buried inside the protein and acts as an anchor to keep the coenzyme at the right position during catalysis. Also, the PLP-LYS internal aldimine was found to favor the ketoenamine tautomer over the enolimine tautomer at the active site of SHMT . In this paper, the transimination reaction is studied for SHMT starting from the ketoenamine form of the PLP-LYS internal aldimine by employing hybrid quantum mechanical/molecular mechanical (QM/MM) simulations , combined with the metadynamics method of rare event sampling. Specifically, we have studied the free energy landscape and mechanism of the transimination reaction for conversion of PLP-LYS (SHMT) internal aldimine to the PLP-serine (substrate) external aldimine at the active site of the SHMT enzyme in aqueous medium.…”
Section: Introductionmentioning
confidence: 99%
“…The initial 345-nm peak formed upon L-cysteine binding to H123A SufS is assigned as the enolimine tau-tomer of the Cys-aldimine that is slightly red-shifted by loss of the nearby histidine and itsstacking interaction. This assignment is also consistent with known PLP chemistry because the enolimine is predicted to be the more reactive of the Cys-aldimine tautomers and would logically proceed to the Cys-ketimine seen at 350 nm (35,36).…”
Section: Role Of His-123 and Cys-364 In The Sufs Mechanismsupporting
confidence: 81%
“…3-5). A similar phenomenon is predicted by metadynamics calculations carried out on the PLP-dependent serine hydroxymethyltransferase (SHMT) enzyme (35). Those previous studies suggested that theinteraction of the PLP pyridine ring with SHMT His-122 is weakened in the enolimine tautomer of the external aldimine of SHMT.…”
Section: A Role For His-123 As An Acid-base Catalystsupporting
confidence: 72%
“…(1 mM) reduces the Schiff-base between the protein and PLP, resulting in a noticeable reduction in absorbance at 425 nm (Soniya and Chandra, 2018;Toney, 2011). Treatment of as-purified LpThi5…”
Section: Primer Name Sequencementioning
confidence: 99%